Impairment of Retention But Not Acquisition of a Visuomotor Skill Through Time-Dependent Disruption of Primary Motor Cortex - Hadipour-Niktarash, Arash (J Neurosci, 2007)
Learning a visuomotor skill involves a distributed network which includes the primary motor cortex (M1). Despite multiple lines of evidence supporting the role of M1 in motor learning and memory, it is unclear whether M1 plays distinct roles in different aspects of learning such as acquisition and retention. Here, we investigated the nature and chronometry of that processing through a temporally specific disruption of M1 activity using single-pulse transcranial magnetic stimulation (TMS). We applied single-pulse TMS to M1 or dorsal premotor cortex (PMd) during adaptation of rapid arm movements (∼150 ms duration) to a visuomotor rotation. When M1 was stimulated either immediately after the end of each trial or with a 700 ms delay, subjects exhibited normal adaptation. However, whereas the memory of the subjects who received delayed-TMS showed normal rates of forgetting during deadaptation, the memory of those who received immediate TMS was more fragile: in the deadaptation period, they showed a faster rate of forgetting. Stimulation of PMd with adjusted (reduced) intensity to rule out the possibility of coactivation of this structure caused by the current spread from M1 stimulation did not affect adaptation or retention. The data suggest that, during the short time window after detection of movement errors, neural processing in M1 plays a crucial role in formation of motor memories. This processing in M1 may represent a slow component of motor memory which plays a significant role in retention.